TOTAL PLATE NUMBER OF BACTERIA AND NON-COLIFORM BACTERIA NUMBER IN HEALTHY DOG AND DIARRHEA - Pradipta, Indra Manik; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana; Vol. 15 No. 3 June 2023, 2022)
This study aims to determine the total bacterial plate count and the number of non-coliform bacteria in healthy and diarrheal dogs isolated from dog feces at the Denpasar and Badung veterinary clinics. The samples used were fresh feces from healthy dogs and diarrhea with a total of 20 samples (10 healthy and 10 diarrheal). The method of this study was carried out by isolating bacteria on Nutrient Agar media using the pour method for total plate number of bacteria and Eosin Methylene Blue Agar media using the scatter method for non-coliform bacteria. The data obtained were tested using the Independent T Test. The results showed the number in healthy dogs was 3.7 x 10 7 (CFU/g) for ALTB and 1.5 x 10 7 (CFU/g) for non-coliform bacteria, while in diarrhea dogs it was 1.5 x 10 9 (CFU/g) for ALTB and 7.3 x 10 7 (CFU/g) for non-coliform bacteria. From the results of the study, it was concluded that ALTB and the number of non-coliform bacteria had a significant difference between healthy dogs and diarrhea in which healthy dogs had fewer bacterial colonies than diarrhea dogs which had more bacterial colonies (P?0,05). Further research is needed regarding the effect of non-coliform bacteria from dogs on the surrounding environment.